Identification of New Lupane-Type Triterpenoids as Inverse Agonists of RAR-Related Orphan Receptor Gamma (RORγ) - Schwarz, Patrik F.; Perhal, Alexander F.; Guder, Famke; González, Jorge Enrique Hernández [UNESP]; Janssen, Kerrin; Sağıroğlu, Ece; Tahir, Ammar; Kirchmair, Johannes; Rochel, Natacha; Dirsch, Verena M.; Chen, Ya (American Chemical Society (ACS), 2025)
Targeting retinoic acid-related orphan receptor γ (RORγ) with inverse agonists presents a promising therapeutic strategy for treating autoimmune diseases, including psoriasis, rheumatoid arthritis, and multiple sclerosis. Through structure-based virtual screening, we identified a lupane-type pentacyclic triterpenoid, (2Z)-2-(2-furanylmethylene)-3-oxolup-20(29)-en-28-oic acid (15), as a new inverse agonist of RORγ. The compound exhibited IC50 values of 0.4 μM and 0.9 μM in Gal4-RORγ and full-length RORγ luciferase assays, respectively. Compound 15 showed improved potency and efficacy compared to a structurally related known inverse agonist, betulinic acid. Among the four additional analogues tested (15.1-15.4), two (15.2 and 15.3) also demonstrated RORγ inverse agonist activity with low micromolar IC50 values in Gal4-RORγ luciferase assay. Real-time quantitative polymerase chain reaction experiments confirmed that compounds 15, 15.2, and 15.3 downregulated RORγ target genes. Thermal shift assays showed that both betulinic acid and 15 stabilized the RORγ ligand-binding domain. Molecular docking and structure-activity relationship analysis revealed distinct binding modes within the RORγ ligand-binding domains, further supported by site-directed mutagenesis. These findings expand the repertoire of RORγ inverse agonists based on the pentacyclic triterpenoid scaffolds.